2006
DOI: 10.1021/jp066328h
|View full text |Cite
|
Sign up to set email alerts
|

On the Structure of Au/Pd Bimetallic Nanoparticles

Abstract: We performed a study on bimetallic Au/Pd nanoparticles using aberration corrected electron microscopy along with molecular dynamics simulations to investigate the features of specific atomic sites at the surface, which can be related to the high catalytic activity properties of the particles. The calculations mimic the growth of nanoparticles through a cooling process from a molten solid to a crystalline structure at room temperature. We found that the final structure for the alloy particles is neither a cuboc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 18 publications
8
70
0
1
Order By: Relevance
“…Thus, former MD studies on Au and Au/Pd nanoparticles confirm the appearance of a hysteresis loop in the melting-freezing cycle, [12][13][14] and that the melting temperature of the Au nanoparticles strongly depends on the size of the cluster. 15 Recently, Chen et al 16 investigated the melting transition of Ag/Au small particles (n ) 55), and constructed a transition phase diagram that may be contrasted with experiments using particles of the same size.…”
Section: Introductionmentioning
confidence: 75%
“…Thus, former MD studies on Au and Au/Pd nanoparticles confirm the appearance of a hysteresis loop in the melting-freezing cycle, [12][13][14] and that the melting temperature of the Au nanoparticles strongly depends on the size of the cluster. 15 Recently, Chen et al 16 investigated the melting transition of Ag/Au small particles (n ) 55), and constructed a transition phase diagram that may be contrasted with experiments using particles of the same size.…”
Section: Introductionmentioning
confidence: 75%
“…6 Using CO as the probing molecule, Luo et al 6 identified the isolated Pd sites as a unique surface ensemble on PdAu clusters supported on SiO 2 . Through TEM observations and molecular dynamics ͑MD͒ simulations, Mejia-Rosales et al 12 also found that the most common site on the surface of PdAu cluster comprises a hexagonal array of gold atoms with a Pd atom in the center.…”
Section: Resultsmentioning
confidence: 99%
“…10͒. Using the aberration corrected electron microscopy, Mejia-Rosales and co-workers 11,12 observed that the final structure of Pd-Au alloyed particles is neither cuboctahedral nor icosahedral but has very rough surfaces with isolated Pd sites surrounded by Au atoms. Very few structural analyses have been reported for supported PdAu nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in atomic numbers is but a good reason to use HAADF-STEM. 414 Figure 34 shows various structure types of AuPd bimetallic nanoparticles on activated carbon and TiO 2 supports, respectively. 326 Alloy structure (Figure 34a, b), Pdcore/Au-shell (Figure 34c, d), and Au-core/Pd-shell ( Figure 34e, f) morphologies can be clearly identified.…”
Section: Structure and Dynamics Of Bimetallic Particlesmentioning
confidence: 99%